PHONOLOGICAL INTERFERENCE OF MADURESE TOWARDS ENGLISH AT THE ELEVENTH STUDENTS OF SMA AL HIKAM BANGKALAN EAST JAVA - Muhassin, Mohammad; Ansar, Fithrah Auliya; Putri, Prasasti Prasetyo (English Education: Jurnal Tadris Bahasa Inggris, 2018)
Phonological interference is a common types of interference, its most prominent manifestation being a ‘foreign accent’. Phonological interference happens when the speaker pronounces the English words, then the word are interfered with other sounds of native language. Madurese as a native language in Madura Island have unique characteristics. Based on the interview result of the teacher, at the eleventh students when pronouncing English, there were some differences from English Standard. The pronouncing of English in those words have been influenced by the sounds of phonemes in Madurese. The aim of this research is to find out the types of students’ phonological interferences, the percentages of phonological interference of madurese students in SMA Al Hikam Bangkalan East Java. It is only focused on phonological aspects or accent. The method of the research is used descriptive-qualitative. The result shows that there are 5 types of students phonological interference and the total of students’ phonological interference is 52,93 % represent 699 phonolohical interference. The highest phonological interference frequency made by the students is sound replacements.Keywords: Phonological Interference, Madurese students’, Accent, Pronunciation